Micro-entrepreneurs strategies to revitalise firm performance amid economic uncertainty - Mohd Sam, Mohd Fazli; Ismail, Albert Feisal @ Muhd Feisal; Md. Taib, Mohd Syafiq; Alias, Siti Nur Aisyah; Mohamed, Nurul Hasyimah (International Journal of Research and Innovation in Social Science, 2025)
Micro and small enterprises in the entrepreneurial sector are essential to the process of economic growth in both developed and developing nations. However, microenterprise is more vulnerable to the current economic climate and uncertainties because they are young and have fewer liabilities. From 2017 to 2021, micro entrepreneurs in Malaysia faced various challenges due to economic uncertainty which were political uncertainty, trade policy uncertainty, exchange rate uncertainty, and the COVID-19 pandemic. They should be able to adapt and implement effective strategies to be better positioned to succeed and grow their businesses. The purpose of this study is to investigate the micro entrepreneur strategies to revitalise business performance in the face of economic uncertainty. The key micro entrepreneur strategies chosen for this study include supply chain management, cash flow management, digital marketing, diversification, and risk management. 5 micro entrepreneurs have been interviewed to get the results. By using MAXQDA software, the researcher can identify the relationship between micro entrepreneur strategies and business performance. In this study, will use a descriptive research design and a qualitative methodology. The research strategy for the study is through the interview. Based on the MAXQDA result, Respondent A, B, D, and E has utilised all five key micro entrepreneur strategies which are supply chain management, cash flow management, digital marketing, diversification, and risk management to revitalise their business performance in the face of economic uncertainty. According to the data analysis, all the variables are significant towards business performance, and the result is that supply chain management, cash flow management, and diversification are the most influencing strategies that influence business performance. However, Respondent C has utilised three key micro entrepreneur strategies which are supply chain management, cash flow management, and diversification to revitalise their business performance in the face of economic uncertainty. Given this, government and micro entrepreneurs recommend considering all five key micro entrepreneur strategies for promoting a culture of innovation and resilience within the small business community and for nurturing a culture of continuous improvement and adaptation for their business.